The Effect of Cognitive Behavioral Therapy Games on Students’ Work Resilience - Lu'lu'il Maknun; Didik Nurhadi; Yoto yoto (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2025)
This study aims to analyze the effect of a Cognitive Behavioral Therapy Game (CBT Game) on the work resilience of vocational high school students. This study used a quantitative approach with a quasi-experimental pretest–posttest control group design. The participants were 16 male Grade X students from the Automotive Engineering Program at SMKN 1 Rejotangan, divided into experimental and control groups. The experimental group received behavioral counseling using a Cognitive Behavioral Therapy Game (CBT Game), whereas the control group received conventional counseling. Data were collected using a work resilience scale, observations, and interviews. The data were analyzed using descriptive and comparative statistics to assess differences in work resilience improvement between the two groups. The results showed that the CBT Game significantly improved students’ work resilience. The mean work resilience score in the experimental group increased from 48.8 to 66.25, whereas that in the control group increased from 56.1 to 60.6. In addition, students responded positively to the CBT Game, as indicated by increased motivation, engagement, and self-reflection during the counseling process. These findings indicate that the CBT Game can serve as an effective innovation in guidance and counseling services to help vocational high school students develop work resilience as part of their preparation for entering the workforce